From acylethynylpyrroles to pyrrole-pyrone ensembles in a one step. Issue 40 (3rd October 2019) - Gotsko, Maxim D.; Saliy, Ivan V.; Sobenina, Lyubov' N.; Ushakov, Igor A.; Trofimov, Boris A.
Graphical abstract: Highlights: Previously unknown functionalized pyrrole-pyrone ensembles have been synthesized in up to 87%. [4+2]-Cyclization of available acylethynylpyrroles with methylene active esters. Yield of the target ensembles depended on the nature of the base. Abstract: Functionalized pyrrole-pyrone ensembles have been synthesized in up to 87% yields by KOH/MeCN [4+2]-cyclization of available acylethynylpyrroles with methylene active esters. The synthesized compounds, due to their potential rich chemistry, are rewarding building blocks for novel pyrrole-integrated complex molecules and promising precursors of medicine targeted compounds.